Ferric Chloride: An Eco-friendly Catalyst for the Stereoselective Synthesis of 2-Deoxy Aryl-O-Rhamnosides - Qiu, Saifeng; Sun, Guosheng; Ding, Zekun; Chen, Heshan; Zhang, Jianbo (Synlett, 2017)
A facile and direct O-glycosylation method for the stereoselective synthesis of 2,6-dideoxy α-O-aryl-glycosides has been described using an eco-friendly catalyst, ferric chloride (FeCl3). The approach can be applied to a wide range of differently substituted phenols including not only mono-substituted ones bearing electron-donating and electron-withdrawing groups but also disubstituted ones. Ultimately, 2,6-dideoxy aryl-O-glycosides were obtained rapidly (<30 min) in good to excellent yields (52–88%) with sole α-selectivity.
Keywords: FeCl3; stereoselective synthesis; O-glycosylation; aryl glycosides; 2-deoxy rhamnosides